Determinação da carga parasitária por PCR semiquantitativa em diferentes tecidos de cães naturalmente infectados por Leishmania(Leishmania) chagasi e sua associação com sinais clínicos da doença. - Carvalho, Cristiane Costa de (2007)
The municipal district of Raposa located in the State of Maranhão, Brazil, is an endemic area of human and canine visceral leishmaniasis. Dogs are considered to be the principal Leishmania chagasi reservoir in this location. The objective of this study was to examine the relative levels of parasitic DNA in different tissues of infected dogs and their association with clinical signs of Leishmaniasis. We initiated this study by collecting blood samples from 233 distinct dogs that were analyzed by means of serological diagnosis. Of all examined dogs, 69 were positive in the anti-Leishmania ELISA. According to technical reasons only 27 of the Leishmania infected dogs could be recaptured and studied. The animals were classified according to their clinical signs in asymptomatics (10 animals), oligosymptomatics (8 animals) and polysymptomatics (9 animals) groups. A quantitative PCR method was developed and established in order to examine the parasitic load in blood, bone marrow, lymph node, spleen and skin. The parasite could be detected in lymph nodes of all animals analyzed (100%). The tissue with the highest parasitic load was lymph nodes followed by spleen, blood, bone marrow and skin. Comparing all analyzed tissues, the lymph nodes presented the highest levels of parasitic DNA, without exception, regardless their symptoms classification. Contrary to various other studies, we have detected the lowest parasitic DNA concentration in skin tissues. The quantitative PCR assay established in this study was sensitive, fast and inexpensive for qualitative and quantitative analyses of the Leishmania chagasi DNA. The canine lymph node is the most frequently infected tissue, with greater levels of parasitic DNA, and may be considered a target tissue for leishmaniasis monitoring in dogs.